Avaliação da histotoxicidade e de alterações metabólicas após o uso do etil-cianoacrilato e n-butil cianoacrilato em camundongos - Simon, Caroline Ferreira (2011)
The cyanoacrylate derivatives have been extensively used as tissue adhesives in wound. Among the most widely used adhesives are the n-butyl cyanoacrylate , which is a compound of long chain and the ethyl-cyanoacrylate which is an acid cyanoacrilic ester of short chain. The objective of this study was evaluated the hepatic, renal and cutaneous toxicity of ethyl-cyanoacrylate and n-butyl cyanoacrylate in mouse. 84 mouse of swiss albino strain were used and divided in three groups, each with 28 animals. A longitudinal incision was made to three centimeters on the back of each mouse. In these animals, the syntheses was realized with ethyl-cyanoacrylate (group A), with n-butyl cyanoacrylate (group B) and suture with náilon monofilament yarn (group C), the control group. Sample were collected at 7, 15, 30 and 45 days after treatment for biochemical examination of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase, creatinine, urea and for histopathological examination was collected liver, kidneys and animals skin. During the experiment was significant difference between groups in mean of ALT at 30 (p=0,039) and 45 days (p=0,0391), AST at 45 days (p=0,0000) and creatinine at 15 (p=0,0169) and 45 days (p=0,0062). In the histopathological examination were not observed changes in toxicity indicatives in the kidneys, liver, skin. In the studied condition not been demonstrated kidney or liver toxicity in the use of ethyl-cyanoacrylate and n-butyl cyanoacrylate for skin syntheses.